Antimicrobial and Genetic Profiles of Vibrio vulnificus and Vibrio parahaemolyticus Isolated From the Maryland Coastal Bays, United States - da Silva, Ligia V.; Ossai, Sylvia; Chigbu, Paulinus; Parveen, Salina (Frontiers in Microbiology, 2021)
Vibrio vulnificus (Vv) and Vibrio parahaemolyticus (Vp), found naturally in marine and estuarine environments, are the leading cause of seafood associated gastrointestinal illness and death. Consumption of improperly cooked crabs and handling of live crabs are potential routes of exposure to pathogenic bacteria such as Vv and Vp. Little information is available on serotype, genetic and antimicrobial profiles of Vv and Vp recovered from Maryland estuaries. The aim of the present study was to determine the serotype of Vp evaluate antimicrobial susceptibility and genetic profiles of Vv and Vp isolated from water, sediment and blue crabs collected from the Maryland Coastal Bays. One hundred and fifty PCR confirmed Vp including 52 tdh+ (pathogenic) and 129 Vv strains were tested for susceptibility to twenty different antibiotics chosen by clinical usage for Vibrio. The O serogroups were determined using an agglutination test with Vp antisera. Pulsed-field gel electrophoresis (PFGE) was used for molecular subtyping to investigate the genetic diversity among tested strains. The most prevalent serotypes were O5 (33.3%), O3 (the pandemic strains, 18.7%) and O1 (14.7%). More than 41% of all tested Vibrio isolates were resistant to three or more antibiotics. Cephalothin showed the highest resistance (42% and 61%), followed by cefoxitin (42% and 31%) and ceftazidime (36% and 29%) for Vv and Vp respectively. Most strains (99-100%) were susceptible to ampicillin/sulbactam, levofloxacin, piperacillin, piperacillin/tazobactam, and tetracycline. Vv and Vp isolates demonstrated a high genetic diversity and 31% of Vv and 16% of Vp strains were PFGE untypeable. No correlations were found among pathogenicity, genetic and antimicrobial resistance profiles of both species of Vibrio. The observed high multiple drug resistance of Vv and Vp from blue crab and its environment is of public health concern. Therefore, there is a need for frequent antibiotic sensitivity surveillance for Vibrio spp.